PENINGKATAN HASIL BELAJAR MATEMATIKA SISWAMELALUI PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY PADA MATERI SEGIEMPAT DI KELAS VIIB SMP NEGERI 24 SAMARINDA TAHUN AJARAN 2012/2013 (THE IMPROVEMENT OF MATHEMATICS LEARNING OUTCOMES THROUGH COOPERATIVE LEARNING COURSE REVIEW HORAY MATERIAL ASPECTS IN FOUR IN CLASS VII BÂ JUNIOR HIGH SCHOOL 24Â SAMARINDA ACADEMIC YEAR 2012/2013) - , Azainil (Jurnal Penelitian Pendidikan Matematika dan Sains, 2013)
The purpose of this study was to determine the improvement of mathematics learning outcomes through cooperative learning course review horay Material Aspects In Four In Class VII B 24 Samarinda junior academic year 2012/2013 . Subjects in this study were students of class VII B Junior High School 24 in Samarinda , amounting to 29 students and the object of this study is the type of cooperative learning course review horay . Data collection techniques using Task Sheet ( LT ) , observation sheets to students and teachers as well as the achievement test . This study was conducted in three cycles . Each cycle of meetings held three times with twice the learning process and one achievement test . Analysis using descriptive statistics such as mean , percentages , and diagrams . The survey results revealed an increase in learning outcomes at each cycle as follows : the average value of the base to the first cycle increased the average value of learning outcomes by 1.84 % of the average value of 62.68 into 64.58 basis and the percentage of completeness of 10.34 % . I cycle to cycle II has increased the average value of the learning outcomes of 7.40 % of the average value of the first cycle of learning outcomes , ie 64.58 becomes 72.11 and 31.03 % for the percentage of completeness . Cycle II to III increased cycle average value of learning outcomes for 7.70 % of the average value of the second cycle of learning outcomes , ie 72.11 into 79.40 and 89.66 % for the percentage of completeness . Judging from the increase in the average increase in each cycle , it can be said that the average points of the basic values ââincreased in the first cycle to 17.41 . Second cycle of 21.72 and the third cycle of 22.06 . In addition , all teachers in the first cycle were considered sufficient , second cycle and third cycle assessed both considered good . While the activities of students in the first cycle is considered less , cycle II assessed fairly , and the third cycle is considered good . Based on these results it can be concluded that the type of cooperative learning chourse review horay. Learning outcomes in mathematics rectangular material in class VII B SMPN 24 Samarinda has increased. Keywords: Improvement , Learning Outcomes , Learning Course Review Horay .